1985
DOI: 10.1136/gut.26.6.562
|View full text |Cite
|
Sign up to set email alerts
|

Acetate absorption and metabolism in the rabbit hindgut.

Abstract: SUMMARY Acetate disappearance from the loops of the hindgut in the rabbit was evaluated by measuring variations in the concentration of acetate in caecocolonic loops and differences in the arterial and venous plasma. In vivo metabolism in gut and liver tissues was studied after introduction of (1-'4C) acetate into caecocolonic loops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Rates of H2/CO 2 acetogenesis ranged from 0.3 to 7.7/tmol acetate per g cecal contents per h, depending on the animal and the method of assay. Since acetate can be absorbed from the rodent cecum and oxidized for energy [8,9], these data taken together with those of Yang et al [8] on the contribution of cecal acetate to rat nutrition, suggest that H2/CO 2 acetogenesis in rat ceca could support up to 0.25% of the animal's maintenance energy requirement. Recently, Lajoie et al [10] confirmed the findings of Prins and Lankhorst by using rat fecal contents, but they also found that rats from their colony were moderately methanogenic.…”
Section: Rodentsmentioning
confidence: 70%
“…Rates of H2/CO 2 acetogenesis ranged from 0.3 to 7.7/tmol acetate per g cecal contents per h, depending on the animal and the method of assay. Since acetate can be absorbed from the rodent cecum and oxidized for energy [8,9], these data taken together with those of Yang et al [8] on the contribution of cecal acetate to rat nutrition, suggest that H2/CO 2 acetogenesis in rat ceca could support up to 0.25% of the animal's maintenance energy requirement. Recently, Lajoie et al [10] confirmed the findings of Prins and Lankhorst by using rat fecal contents, but they also found that rats from their colony were moderately methanogenic.…”
Section: Rodentsmentioning
confidence: 70%
“…The problem is that each SCFA is metabolized differently and at several sites in the body (colonic epithelium, liver, peripheral tissue) (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and the prospects of obtaining blood from the portal vein in volunteers is ethically controversial. An alternative approach is to use an in vitro faecal incubation system, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The VFA appear to provide a regular source of energy for the colonocyte. It is now well established that these bacterial metabolites are partly metabolized in the rabbit colonocyte in the order: butyrate =propionate > acetate; their complete oxidation to carbon dioxide is often the main catabolic pathway Marty et al 1985;. A preferential utilization of butyrate by the large intestine in the human, rat (Roediger, 1980(Roediger, , 1982, guinea-pig ; pig (Rerat et al 1985) has also been suggested.…”
Section: Discussionmentioning
confidence: 99%